BUILDING MUZAKKI LOYALTY THROUGH TRANSPARENCY AND ACCOUNTABILITY: AN ANALYSIS OF MUZAKKI SATISFACTION AT BAZNAS SOUTH KALIMANTAN - Jaya, Fanlia Prima; Suryani, Sri; Firdaus, Firdaus; Kamsariaty, Kamsariaty (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to determine the influence of the variables of Transparency and Accountability on Muzakki Loyalty through Muzakki Satisfaction in BAZNAS South Kalimantan Province; the type of data used in this study is quantitative data; this research is included in the category of causal research, the method used is the Explanatory survey method. The population in this study is all permanent Muzakki recorded in BAZNAS South Kalimantan Province, which is 1,108 Muzakki people; then, in determining the size of the sample using the Harun Al-Rasyid formula, it can be known that the minimum sample size is 164 Muzakki as respondents. The Data Analysis technique used is Path Analysis using SmartPLS Version 4.0. The results of this study found that partially, Transparency and accountability affect Muzakki satisfaction, accountability has an effect on Muzakki loyalty, but Transparency has no impact on Muzakki loyalty simultaneously Transparency and accountability have a significant impact on Muzakki loyalty through Muzakki satisfaction in BAZNAS South Kalimantan Province Keywords: Transparency; Accountability; Muzakki satisfaction; Muzakki Loyalty